Cognitive Trajectories after Postoperative Delirium - Saczynski, Jane S. (2012)
BACKGROUND: Delirium is common after cardiac surgery and may be associated with long-term changes in cognitive function. We examined postoperative delirium and the cognitive trajectory during the first year after cardiac surgery. METHODS: We enrolled 225 patients 60 years of age or older who were planning to undergo coronary-artery bypass grafting or valve replacement. Patients were assessed preoperatively, daily during hospitalization beginning on postoperative day 2, and at 1, 6, and 12 months after surgery. Cognitive function was assessed with the use of the Mini–Mental State Examination (MMSE; score range, 0 to 30, with lower scores indicating poorer performance). Delirium was diagnosed with the use of the Confusion Assessment Method. We examined performance on the MMSE in the first year after surgery, controlling for demographic characteristics, coexisting conditions, hospital, and surgery type. RESULTS: The 103 participants (46%) in whom delirium developed postoperatively had lower pre-operative mean MMSE scores than those in whom delirium did not develop (25.8 vs. 26.9, P<0.001). In adjusted models, those with delirium had a larger drop in cognitive function (as measured by the MMSE score) 2 days after surgery than did those without delirium (7.7 points vs. 2.1, P<0.001) and had significantly lower postoperative cognitive function than those without delirium, both at 1 month (mean MMSE score, 24.1 vs. 27.4; P<0.001) and at 1 year (25.2 vs. 27.2, P<0.001) after surgery. With adjustment for baseline differences, the between-group difference in mean MMSE scores was significant 30 days after surgery (P<0.001) but not at 6 or 12 months (P = 0.056 for both). A higher percentage of patients with delirium than those without delirium had not returned to their preoperative baseline level at 6 months (40% vs. 24%, P = 0.01), but the difference was not significant at 12 months (31% vs. 20%, P = 0.055). CONCLUSIONS: Delirium is associated with a significant decline in cognitive ability during the first year after cardiac surgery, with a trajectory characterized by an initial decline and prolonged impairment. (Funded by the Harvard Older Americans Independence Center and others.)